Konstruksi Pendidikan Karakter Bagi Mahasiswa Di Pondok Pesantren (Studi kasus di Pondok Pesantren Mahasiswa Khoirul Huda Surabaya) - Warsito, Edi (Balai Diklat Keagamaan Surabaya, 2022)
The problem formulation of this research is 1) How is the description of character education construction that was implemented in Pondok Pesantren Khoirul Huda, and 2) How is the implication of character education in Pondok Pesantren Khoirul Huda in a matter of honesty and discipline. Based on these problems, the author tries to research, character education for students in the metropolitan city, especially in the Khoirul Huda Student Islamic Boarding School in Surabaya in constructing educational character for their students, and the implications of character education at the Khoirul Huda Islamic Boarding School in Surabaya for students in a matter of honesty and discipline. This research uses a qualitative descriptive method with a single research strategy. Sources of data used in this study are informants, Place, events, and documentation. The data technique used was observation, interview, and document analysis. The data validity used data triangulation. Meanwhile, the data analysis uses an interactive model that is divided into data, data reduction, data collection, and data collection. The results of this research indicate that the Khoirul Huda Islamic Boarding School in Surabaya emphasizes character teaching followed by character habituation by practicing it. The education activity consists of the classical lecture that focuses on cognitive improvement with habituation of good deeds during the class. The asatidzs and boarding school management are also giving models and guidelines of good deeds in student's daily life. In the process of education, all the educator is helped either from inside or outside boarding school. And the implication of the education process is students able to practice the character of Six characters sublime and able to internalize the value of Tri Success The Next Generation which is manifested in “professional-religious” Keywords: Character, construction, Islamic boarding school